2007
DOI: 10.1148/radiol.2432060353
|View full text |Cite
|
Sign up to set email alerts
|

Teniae Coli–based Circumferential Localization System for CT Colonography: Feasibility Study

Abstract: This HIPAA-compliant study, with institutional review board approval and informed patient consent, was conducted to retrospectively develop a teniae coli-based circumferential localization method for guiding virtual colon navigation and colonic polyp registration. Colonic surfaces (n = 72) were depicted at computed tomographic (CT) colonography performed in 36 patients (26 men, 10 women; age range, 47-72 years) in the supine and prone positions. For 70 (97%) colonic surfaces, the tenia omentalis (TO), the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 12 publications
0
30
1
Order By: Relevance
“…For example, in the studies [30][31], the folds were detected by thresholding the curvatures in the 3D colon representation, while in [32], the detection task was fulfilled by using a Gabor filter on a 2D unfolded colon representation. In this exploratory investigation, a local elevation mapping (LEM) method is proposed for the colonic fold detection and segmentation.…”
Section: Haustral Folds Detection and Segmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the studies [30][31], the folds were detected by thresholding the curvatures in the 3D colon representation, while in [32], the detection task was fulfilled by using a Gabor filter on a 2D unfolded colon representation. In this exploratory investigation, a local elevation mapping (LEM) method is proposed for the colonic fold detection and segmentation.…”
Section: Haustral Folds Detection and Segmentationmentioning
confidence: 99%
“…In the previously reported literature, approaches for TC extraction can be categorized into two groups, manual drawing and automatic extraction [30][31] [32]. As far as the automatic approaches to be concerned, most of the previous studies suggested to use curvature filter or Gabor filter [32] for surface analysis to get the TC lines on the colon.…”
Section: Teniae Coli Extraction For Colonmentioning
confidence: 99%
“…13, we selected TO from the manually labeling results provided by radiologist, then derived the corresponding TM and TL in one-third of the circumference location of the colon. When calculating the RMSE of their method, 13 only TM and TL were measured, since the TO itself was the reference standard. The proposed method achieved an average normalized RMSE ( 6 standard deviation, [95% confidence interval]) of 4.87% ( 6 2.93%, [4.05% 5.69%]), while Huang's method 13 had an average normalized RMSE of 5.65% ( 6 1.94%, [5.60% 5.71%]).…”
Section: Teniae Coli Indentification Based On Icvmentioning
confidence: 99%
“…When calculating the RMSE of their method, 13 only TM and TL were measured, since the TO itself was the reference standard. The proposed method achieved an average normalized RMSE ( 6 standard deviation, [95% confidence interval]) of 4.87% ( 6 2.93%, [4.05% 5.69%]), while Huang's method 13 had an average normalized RMSE of 5.65% ( 6 1.94%, [5.60% 5.71%]). The difference between these two methods is not statistically significant (p ¼ 0.08).…”
Section: Teniae Coli Indentification Based On Icvmentioning
confidence: 99%
See 1 more Smart Citation